A Learning Philosophy That Enjoys Students Regarding Religious Ceremonies And Ecotheology In The Bhagavad-Gita - Ni Wayan Gateri; I Ketut Subagiasta (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2026)
Hindu devotees are obligated to perform the Tumpek Pengatag ceremony on Saturday Kliwon Wariga, for the fertility and prosperity of vegetation. Ecotheologically, Hindus cherish the environment by worshiping the Almighty God in his image as Sang Hyang Pasupati. Through His power, He created all plants useful for offerings or offerings during the holy day of Galungan every Buddha Kliwon Dunggulan, such as coconuts, bananas, mangoes, mangosteens, flowers, and other plants. This is a manifestation of Hindu devotion to God Almighty and to environmental sustainability, for the sake of beauty and a pristine environment, for the well-being and prosperity of Hindus in a fertile and prosperous universe on our beloved land, Indonesia.